Frequency of ABO Blood Group and its Association with Acute Coronary Syndrome in Patients Presenting in a Tertiary Care Center of Nepal - Pathak, Surya R; Jha, Sunil C; Gajurel, Ratna M; Poudel, Chandra M; Shrestha, Hemant; Thapa, Sanjeev; Sahi, Ravi; Thapa, Shovit; Koirala, Paras (Journal of Institute of Medicine Nepal, 2020)
Introduction Coronary artery disease is the major cause of death all over the world. There are studies suggesting association between blood group and coronary artery disease. We attempted to study the frequency of ABO blood group and its association with acute coronary syndrome (ACS) in our hospital. Methods This is a retrospective, cross sectional study carried out in Manmohan Cardiothoracic Vascular and Transplant Centre from March 2018 to February 2019. Patients who were admitted with diagnosis of ACS were enrolled in the study. Data were recorded and analyzed using SPSS 20. Association between blood group and ACS was analyzed using chi square test and logistic regression. Results Total 430 patients were admitted with diagnosis of ACS during the study period, of which 307 (71.4 %) were male and Mean age was 61.22 years (±10.75). Blood group O was the most common type of blood group observed in 207 (48%) patients. ACS was significantly higher in blood group O compared to other groups after adjusting for normal ABO blood group prevalence in general population: blood group O vs. A (OR: 3.45, 95% CI: 2.48- 4.79, p- <0.001), blood group O vs. B (OR: 5.08, 95% CI: 3.53-7.33, p- <0.001), blood group AB vs. O (OR: 0.65, 95% CI: 0.41- 1.02, p- 0.064). Individuals with blood group O and B had increased risk of having STEMI and NSTEMI where as those with blood group A had increased risk of having unstable angina. Conclusion There was association between ABO blood group and coronary artery disease. Individuals with blood group O have increased incidence of ACS.